Proposta de modelo multicritério para seleção de projetos em uma incubadora - Câmara, Ana Alice da Silva (Universidade Federal Rural do Semi-Árido, 2018)
Decision-making processes are present in all organizations and should always be well evaluated, since a decision made in the wrong way can lead to a number of problems for those involved. In a project incubator, selecting projects to compose the portfolio is one of the organization's most important processes. Therefore, the present work proposed a multicriteria model for the selection of projects in the two initial phases of the incubation process: pre-incubation and incubation. The first model was based on the PROMETHEE GDSS method, because it is a group decision where it is necessary to evaluate the criteria and preferences of all the decision makers. For the model of the incubation stage, the PROMETHEE V method was used, treating it as a single decision maker. As results achieved, it was possible to propose multicriteria models to support the decision-making process in a incubator and to perform the numerical applications of these to prove its robustness and applicability. In the application of the preincubation model, the best evaluated projects were A2, A14 and A16, and the worst evaluated was A17. In the application of the model to the incubation phase, the selected projects were A1, A2, A4, A7, A16 and A17.
Monografia
Keywords: Processo de tomada de decisão; PROMETHEE V; Incubadoras; Multicritério; PROMETHE GDSS; Decision-Making Process; Incubators; Multicriteria; PROMETHEE GDSS; PROMETHEE V; ENGENHARIAS::ENGENHARIA DE PRODUCAO